HUBUNGAN PENGETAHUAN DAN SIKAP IBU DENGAN PENCEGAHAN ISPA PADA BALITA DI PUSKESMAS DATUK BANDAR TAHUN 2018 - NURAINI .; DADY HIDAYAH DAMANIK (JURNAL ILMIAH KOHESI, 2019)
Acute Respiratory Infection (ARI), the acute infection process lasts for 14 days caused by microorganisms and attacks one or more parts of the airways, starting from the nose (upper channel) to the alveoli (lower channel), including adnexanya tissue, such as sinuses , middle ear cavity and pleura (MOH RI, 2010). World Health Organization (WHO) 2008 states that ARI is one of the most common causes of death in children in developing countries. These acute respiratory infections cause four of the estimated 15 million deaths in children under 5 years of age each year and as many as two-thirds of these deaths occur in infants.ARI is still one of the main public health problems. This is due to the high mortality rate caused by ARI, especially in infants and toddlers. Each child is estimated to experience 3-6 episodes of ARI. Every year 40% -60% of visits to the Puskesmas are sufferers of ARI. For all under-five deaths, the proportion of deaths caused by ARI reaches 20-30%. ISPA deaths are mostly caused by pneumonia (Riskesdas, 2010).Pneumonia, which was originally a common respiratory infection, because it was not treated properly, eventually led to coughing and breathing difficulties. As many as 150,000 children under five die each year from pneumonia, this is caused by various factors such as geographical, cultural and economic difficulties experienced by the population in reaching health care facilities. It is estimated that 11-22% of children under five suffering from coughing or breathing disorders are not treated at all (Jamal, 2010).